Integrasi Nilai-Nilai Multikultural dalam Memelihara Kerukunan di Tengah Keberagaman Budaya dan Agama di Sangatta Kutai Timur - Husaini, Ahmad Bahrudz; Yakin, Ainul; Mubarok, Ramdanil (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI Sangatta Kab. Kutai Timur., 2025)
This study aims to examine the integration of multicultural values in maintaining social harmony amid cultural and religious diversity in Sangatta, East Kutai. Sangatta is recognised as a multicultural area inhabited by various ethnic groups and adherents of different religions, making it essential to understand how its community preserves social cohesion in daily life. The study employed a descriptive qualitative approach. The findings reveal that harmony in Sangatta is fostered through interreligious and intercultural social interactions, community cooperation (gotong royong), early education on tolerance, community deliberation, and open communication. However, several challenges persist, including limited interaction among specific ethnic or religious groups, the lack of informal intercultural activities, and low youth participation in interfaith engagements. Therefore, it is necessary to strengthen the roles of social institutions such as the Interfaith Harmony Forum (FKUB), increase youth involvement, and organise sustainable intercultural programs. These efforts are vital to reinforcing the foundations of harmony and positioning Sangatta as a model for peaceful multicultural coexistence